A method for preparing a y-type molecular sieve
Patent Information
- Application Number
- CN202410674277.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-05-28
AI Technical Summary
[0004]对于直接法合成高硅Y分子筛,人们最初是在非模板剂体系中合成,即反应凝胶中不加入任何有机模板剂,仅通过调整凝胶配比以及调整晶化时间、晶种或无机导向剂的制备方法等来达到提高Y分子筛硅铝比的目的,但效果并不理想,硅铝比很难达到6
[0027] This invention improves the skeleton silicon-aluminum ratio of molecular sieve products and reduces the crystal size of products by treating the starting Y molecular sieve by changing the type and amount of organic ions. Moreover, the synthesis process is simple and inexpensive, which helps to reduce technical costs and facilitates industrial implementation.
Smart Images

Figure CN118724011B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of molecular sieve synthesis, and more specifically to a method for synthesizing Y molecular sieves using seed crystals loaded with organic matter. Background Technology
[0002] Catalytic cracking (FCC), as a major production unit in petroleum refining enterprises, occupies a very important position in petroleum processing. It is an effective way to achieve deep processing of crude oil, improve the yield, quality and economic benefits of light oil. Catalytic cracking is an important process in the secondary processing of crude oil and is the main production method of liquefied petroleum gas, gasoline, kerosene and oil extraction and diesel. It plays a pivotal role in oil refineries.
[0003] High-silica Y zeolite is a major active component in catalysts for catalytic cracking (FCC) and hydrocracking processes. However, conventionally synthesized Y zeolite has a low silica-alumina ratio, requiring post-processing dealumination to prepare high-silica Y. For nearly 60 years, the direct synthesis of high-silica Y zeolite has remained unsuccessful, becoming a challenging issue in the field of molecular sieve synthesis.
[0004] For the direct synthesis of high-silicon Y molecular sieves, researchers initially synthesized them in a non-templative system, that is, without adding any organic template agent to the reaction gel. They aimed to increase the silicon-to-aluminum ratio of the Y molecular sieve by adjusting the gel ratio, crystallization time, and the preparation method of seed crystals or inorganic directing agents. However, the results were not ideal, and it was difficult to achieve a silicon-to-aluminum ratio of 6.
[0005] The use of organic structure-directing agents has brought the synthesis of Y-zeolites into a new field. In 1987, US Patent 4,714,601 disclosed a polymorph of FAU called ECR-4 with a silicon-to-aluminum ratio greater than 6. It was obtained by hydrothermal crystallization at 70–120°C in the presence of seed crystals, using alkyl or hydroxyalkyl quaternary ammonium salts as template agents. In 1990, US Patent 4,931,267 disclosed a polymorph of FAU called ECR-32 with a silicon-to-aluminum ratio greater than 6. It was obtained by hydrothermal crystallization at 90–120°C using tetrapropyl and / or tetrabutylammonium hydroxide as structure-directing agents, and exhibits high thermal stability.
[0006] CN111825104A discloses a method for preparing a high-silica Y molecular sieve, comprising: a) mixing raw materials containing an aluminum source, a silicon source, an alkali metal source, a nitrogen-containing heterocyclic template agent R, and water to obtain an initial gel; b) adding a silica-alumina molecular sieve seed crystal with a FAR or EMT structure to the initial gel obtained in step a), stirring, and obtaining a synthetic gel; c) crystallizing the synthetic gel obtained in step b). The obtained synthetic molecular sieve exhibits good hydrothermal / thermal stability and can be applied to fluidized catalytic cracking, demonstrating good catalytic activity.
[0007] CN116692894A discloses a binder-free Y-type molecular sieve, the preparation method of which includes: (1) mixing a binder and Y-type seed crystals, molding and calcining to obtain a calcined product; (2) mixing an alkali, a silicon source, a solvent and the calcined product, and carrying out a crystallization reaction to obtain a binder-free Y-type molecular sieve. This molecular sieve achieves efficient adsorption of CO2. Summary of the Invention
[0008] This invention discloses a method for synthesizing Y-type molecular sieves using seed crystals loaded with organic matter as raw materials. The method first treats a Y-type molecular sieve with a high framework silica-to-alumina ratio (hereinafter referred to as high-silicon Y) with a quaternary ammonium compound. Utilizing the protective effect of the quaternary ammonium compound on the molecular sieve framework, protected high-silicon Y-type molecular sieve seed crystals are obtained. Then, the obtained seed crystals are mixed with silicon and aluminum sources and further interact with each other. Under certain hydrothermal conditions, the inductive effect of the high-silicon Y-type molecular sieve seed crystals is fully utilized to obtain the Y-type molecular sieve product. The silica-to-alumina ratio of the Y-type molecular sieve product can be adjusted by changing the conditions of the quaternary ammonium compound treatment of the seed crystals and by selecting different Y-type molecular sieve seed crystals. The applicant has found that, compared with the method of directly synthesizing NaY molecular sieves without the above-mentioned seed crystals, the Y-type molecular sieve synthesized using seed crystals loaded with organic matter as raw materials can significantly accelerate the crystallization reaction process, increase the framework silica-to-alumina ratio of the molecular sieve product, and reduce the crystallite size of the product. Using USY protected with a quaternary ammonium compound as a seed crystal, the higher the content of the quaternary ammonium compound, the higher the framework silica-to-alumina ratio of the Y-type molecular sieve. By adjusting the content of organic matter, the silica-to-alumina ratio of the synthesized Y-type molecular sieve can be controlled.
[0009] The first aspect of this invention discloses a method for preparing Y-type molecular sieves, comprising the following steps:
[0010] (1) The starting Y molecular formula is impregnated with a solution of quaternary ammonium compound to introduce quaternary ammonium ions into the molecular sieve channels and obtain modified Y molecular sieve seed crystals.
[0011] (2) The silicon source, aluminum source, alkali, and Y molecular sieve seed crystals with a protected framework are uniformly mixed with water to obtain a mixed gel;
[0012] (3) The mixed gel is transferred to a high-temperature crystallization vessel for high-temperature crystallization to obtain the Y molecular sieve product.
[0013] In step (1), the Si / Al ratio of the framework of the starting Y molecular sieve is not less than 2.0, preferably not less than 3.0, and more preferably not less than 4.0; there are no special requirements for the crystallinity of the starting Y molecular sieve, preferably 60-110, more preferably 70-100, and most preferably 80-95; the Si / Al ratio is determined by X-ray fluorescence spectroscopy.
[0014] The quaternary ammonium compound mentioned in step (1) is a quaternary ammonium salt or a quaternary ammonium base. Preferably, the quaternary ammonium compound is one or more of tetrapropylammonium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium bromide, tetraethylammonium bromide, and tetramethylammonium bromide. The solvent used in the solution is water or a low-carbon alcohol, preferably one of ethanol, propanol, and ethylene glycol.
[0015] The impregnation method described in step (1) is selected from one or more of the following: excess impregnation method, equal volume impregnation method, multiple impregnation method, impregnation sedimentation method, fluidized bed spray impregnation method, impregnation vapor phase impregnation method, vacuum impregnation method, and pressurized impregnation method.
[0016] The processing conditions in step (1) are as follows, by mass ratio: starting Y molecular sieve: quaternary ammonium compound: solvent = (0.1~1): (0.01~1): (0.01~100); preferably, in the impregnation method described in step (1), the mass ratio of starting Y molecular sieve to quaternary ammonium compound is not less than 0.1, preferably not less than 1, and more preferably not less than 2.
[0017] In step (2), the mass ratio of silicon source: aluminum source: alkali: Y molecular sieve seed crystals with protected framework: H2O is (0.1~1): (0.1~1): (0.01~2): (0.01~1): (0.5~5).
[0018] In step (2), the mass of the Y molecular sieve seed crystals with the skeleton protected is no more than 50% of the total material mass, preferably no more than 30%, and more preferably no more than 20%.
[0019] The silicon source mentioned in step (2) is one or more of tetraethyl orthosilicate, fumed silica, water glass, silica sol, and coarse-pore silica gel.
[0020] The aluminum source mentioned in step (2) is one or more of aluminum sulfate, aluminum nitrate, aluminum powder, sodium aluminate, aluminum hydroxide powder, and boehmite.
[0021] The alkali added to the gel in step (2) is an inorganic alkali or an organic alkali; the inorganic alkali is one or more of LiOH, NaOH, and KOH; the organic alkali is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, choline hydroxide, tetrapropylammonium bromide, hexadecyltrimethylammonium bromide, triethylamine, and ethylenediamine.
[0022] The crystallization temperature in step (3) is 50-120℃, the processing time is 0.1-240h, and the pressure is 0.1-10MPa.
[0023] The crystallization process in step (3) is selected from one or more of hydrothermal crystallization, solid-like phase crystallization, steam-assisted crystallization, and atmospheric pressure rotational crystallization.
[0024] A second aspect of the present invention discloses a catalyst obtained by the preparation method described above.
[0025] A third aspect of the present invention discloses a method for fluidized bed catalytic cracking using the catalyst, wherein the fluidized bed catalytic cracking is carried out in a slurry bed or a fluidized bed, and the feedstock includes, but is not limited to, gas oil, vacuum residue, atmospheric residue, heavy oil, coking tail oil, and coal tar.
[0026] The beneficial effects of the technical solution of this invention:
[0027] This invention improves the skeleton silicon-aluminum ratio of molecular sieve products and reduces the crystal size of products by treating the starting Y molecular sieve by changing the type and amount of organic ions. Moreover, the synthesis process is simple and inexpensive, which helps to reduce technical costs and facilitates industrial implementation. Attached Figure Description
[0028] Figure 1 X-ray diffraction pattern of Example 1 (molecular sieve sample PY-C6.1-TPA25%);
[0029] Figure 2 Scanning electron microscope image of Example 1 (molecular sieve sample PY-C6.1-TPA 25%);
[0030] Figure 3 X-ray diffraction pattern of Example 2 (molecular sieve sample PY-C6.1-TPA 35%);
[0031] Figure 4 Scanning electron microscope image of Example 2 (molecular sieve sample PY-C6.1-TPA 35%);
[0032] Figure 5 X-ray diffraction pattern of molecular sieve sample PY-C6.1-TPABr in Example 3;
[0033] Figure 6 Scanning electron microscope image of Example 3 (molecular sieve sample PY-C6.1-TPABr);
[0034] Figure 7 Compare the X-ray diffraction patterns of the samples; Detailed Implementation
[0035] The following examples are provided to further illustrate the present invention, but are not intended to limit the invention.
[0036] Example 1
[0037] Weigh 2 g of Y molecular sieve (silicon-to-aluminum ratio: 6.1) as the initial Y molecular sieve. Weigh 1.8 g of a 25 wt% tetrapropylammonium hydroxide ethanol solution. Slowly and evenly add the 1.8 g of the above tetrapropylammonium hydroxide ethanol solution into the pores of the molecular sieve at room temperature to impregnate them evenly, obtaining Y molecular sieve seed crystals with a protected framework for later use. Place 5 g of sodium hydroxide in a 150 ml polypropylene bottle and dissolve it in 25 g of deionized water. Stir mechanically for 5 minutes at room temperature until the sodium hydroxide solid is completely dissolved. Add 3.42 g of sodium aluminate to the mixed solution and stir mechanically at room temperature for 30 minutes until the sodium aluminate solid is completely dissolved. Continue to slowly add 50 g of silica sol (30% silica mass fraction alkaline silica sol) and stir mechanically for 1 hour at room temperature until the sol is completely homogeneous. Add 1.5 g of the prepared seed crystals and continue stirring for 1 hour. Seal the sample and crystallize it in an oven at 100°C for 120 hours. After washing and drying, a new Y-type molecular sieve (molecular sieve sample PY-C6.1-TPA25%) was obtained. The X-ray diffraction pattern and scanning electron microscope image of this sample are shown below. Figure 1 and Figure 2 As shown.
[0038] Example 2
[0039] Weigh 2 g of Y molecular sieve (silicon-to-aluminum ratio: 6.1) as the initial Y molecular sieve. Weigh 1.8 g of a 35 wt% tetrapropylammonium hydroxide aqueous solution. At room temperature, slowly and evenly add 1.8 g of the above tetrapropylammonium hydroxide solution into the pores of the molecular sieve to impregnate them evenly, obtaining Y molecular sieve seed crystals with a protected framework for later use. Place 5 g of sodium hydroxide in a 150 ml polypropylene bottle and dissolve it in 25 g of deionized water. Stir mechanically for 5 minutes at room temperature until the sodium hydroxide solid is completely dissolved. Add 3.42 g of sodium aluminate to the mixed solution and stir mechanically for 30 minutes at room temperature until the sodium aluminate solid is completely dissolved. Continue to slowly add 50 g of silica sol (30% silica mass fraction alkaline silica sol), and stir mechanically for 1 hour at room temperature until the sol is completely homogeneous. Add 1.5 g of the prepared seed crystals and continue stirring for 1 hour. Seal the sample and crystallize it in an oven at 100°C for 120 hours. After washing and drying, a new Y-type molecular sieve (molecular sieve sample PY-C6.1-TPA 35%) was obtained. The X-ray diffraction pattern and scanning electron microscope image of this sample are shown below. Figure 3 and Figure 4 As shown.
[0040] Example 3
[0041] Weigh 2 g of Y molecular sieve (silicon-to-aluminum ratio: 6.1) as the initial Y molecular sieve. Weigh 0.5 g of tetrapropylammonium bromide and 1.5 g of water. First, mix the tetrapropylammonium bromide and water to obtain a solution. At room temperature, slowly and evenly add 2 g of the above tetrapropylammonium bromide solution into the pores of the molecular sieve to impregnate it evenly, obtaining a Y molecular sieve seed crystal with a protected framework for later use. Place 5 g of sodium hydroxide in a 150 ml polypropylene bottle and dissolve it in 25 g of deionized water. Stir mechanically for 5 minutes at room temperature until the sodium hydroxide solid is completely dissolved. Add 3.42 g of sodium aluminate to the mixed solution and stir mechanically for 30 minutes at room temperature until the sodium aluminate solid is completely dissolved. Continue to slowly add 50 g of silica sol (30% silica mass fraction alkaline silica sol) and stir mechanically for 1 hour at room temperature until the sol is completely homogeneous. Add 1.5 g of the prepared seed crystal and continue stirring for 1 hour. Seal the sample and crystallize it in an oven at 100°C for 120 hours. After washing and drying, a new Y-type molecular sieve (molecular sieve sample PY-C6.1-TPABr) was obtained. The X-ray diffraction pattern and scanning electron microscope image of this sample are shown below. Figure 5 and Figure 6 As shown.
[0042] Comparative Example 1
[0043] 5g of sodium hydroxide was placed in a 150ml polypropylene bottle and dissolved in 25g of deionized water. The mixture was mechanically stirred for 5 minutes at room temperature until the sodium hydroxide solid was completely dissolved. 3.42g of sodium aluminate was added to the mixture, and the mixture was mechanically stirred for 30 minutes at room temperature until the sodium aluminate solid was completely dissolved. 50g of silica sol (30% silica by mass, alkaline silica sol) was then slowly added dropwise, and the mixture was mechanically stirred for 1 hour at room temperature until the sol was completely homogeneous. 1.5g of USY raw powder (silicon-to-aluminum ratio: 6.1) was added, and stirring was continued for 1 hour. The sample was sealed and crystallized in an oven at 100℃ for 120 hours. After washing and drying, control sample 1 was obtained.
[0044] Comparative Example 2
[0045] 5g of sodium hydroxide was placed in a 150ml polypropylene bottle and dissolved in 25g of deionized water. The mixture was mechanically stirred for 5 minutes at room temperature until the sodium hydroxide solid was completely dissolved. 3.42g of sodium aluminate was added to the mixture, and the mixture was mechanically stirred for 30 minutes at room temperature until the sodium aluminate solid was completely dissolved. 50g of silica sol (30% silica by mass, alkaline silica sol) was then slowly added dropwise, and the mixture was mechanically stirred for 1 hour at room temperature until the sol was completely homogeneous. 1.5g of USY raw powder (silicon-to-aluminum ratio: 2.7) was added, and stirring was continued for 1 hour. The sample was sealed and crystallized in an oven at 100℃ for 120 hours. After washing and drying, control sample 2 was obtained.
[0046] Comparative Example 3
[0047] Weigh 2 g of Y molecular sieve (silicon-to-aluminum ratio: 6.1) as the initial Y molecular sieve. Weigh 1.8 g of pyridine solution with a concentration of 0.5 mg / ml. At room temperature, slowly and evenly add 1.8 g of the above pyridine solution into the pores of the molecular sieve to impregnate it evenly, and then use it as a seed crystal for later use. Place 5 g of sodium hydroxide in a 150 ml polypropylene bottle and dissolve it in 25 g of deionized water. Stir mechanically for 5 minutes at room temperature until the sodium hydroxide solid is completely dissolved. Add 3.42 g of sodium aluminate to the mixed solution and stir mechanically for 30 minutes at room temperature until the sodium aluminate solid is completely dissolved. Continue to slowly add 50 g of silica sol (30% silica mass fraction alkaline silica sol) and stir mechanically for 1 hour at room temperature until the sol is completely homogeneous. Add 1.5 g of the prepared seed crystal and continue stirring for 1 hour. Seal the sample and crystallize it in an oven at 100℃ for 120 hours. After washing and drying, obtain control sample 3.
[0048] Molecular sieve performance testing
[0049] Since the molecular sieves obtained in Comparative Examples 1-3 were amorphous, they could not be characterized by catalytic cracking experiments. Performance tests were conducted using the initial molecular sieve and the Y molecular sieve samples prepared in Examples 1-3.
[0050] Catalyst Preparation: Catalysts for catalytic cracking were prepared using the molecular sieves obtained in Examples 1-3 as raw materials. First, the molecular sieve samples to be tested were dried and cooled. Kaolin, molecular sieves, silica sol, and water were mixed at a mass ratio of 5:4:2:20 at 100°C for 4 hours, then dried at 100°C overnight, followed by hydrothermal aging at 100°C for 4 hours. The resulting sample was pressed into tablets at 20 MPa and sieved to 20-40 mesh to obtain the catalyst for the FCC microreactor. Before evaluating the catalytic reaction, the catalyst bed was filled, and under a nitrogen atmosphere, the temperature was increased to 100°C at a rate of 2°C / min, held at 100°C for 2 hours, then increased to 550°C at a rate of 2°C / min, and calcined at 550°C for 2 hours. Afterward, the temperature was allowed to cool naturally to the reaction temperature for later use. This process constitutes in-situ catalyst activation.
[0051] Catalytic cracking: The catalytic performance of the prepared molecular sieve catalyst was evaluated in this experiment using a fixed-bed reactor of Beijing Weikendu Catalytic Cracking. Nitrogen was used as the carrier gas, and the feed rate was changed by adjusting the nitrogen flow rate, thereby adjusting the space velocity of the reaction. The inner diameter of the reaction tube was 2 cm, and the catalyst loading was 5 g.
[0052] Operating parameters: Reaction temperature: 510℃; Regeneration temperature: 650℃; Carrier gas flow rate: 200mL / min
[0053] Operating steps:
[0054] (1) Use quartz sand and quartz wool to fix the molecular sieve particles at the thermocouple end position in the middle of the reaction tube;
[0055] (2) Install and fix the reaction tube, check the airtightness of the device and related insulation, and ensure that the airtightness and insulation performance of each pipeline are intact;
[0056] (3) Nitrogen gas is introduced into the reaction tube and the temperature is gradually increased to 510℃ to activate the catalyst in situ.
[0057] (4) Adjust to a suitable carrier gas flow rate, and introduce the raw material oil into the reaction tube to contact the catalyst and start the reaction;
[0058] (5) After the reaction is complete, collect the liquid and gaseous products, analyze them by chromatography and calculate the product distribution;
[0059] (6) Start the aging program and raise the temperature to 650℃ for 1 hour. Then repeat steps (3), (4), and (5) for cyclic evaluation.
[0060] The Y molecular sieve (USY molecular sieve in Example 1), which was used as the raw material for preparing the seed crystals, was used as the initial sample 1.
[0061] The performance evaluation of the microreactor in catalytic cracking is shown in Table 1.
[0062] Table 1
[0063]
[0064] As shown in Table 1, Example 2 increased coke yield by 0.01% and propylene yield by 0.23% compared to conventional USY molecular sieve (initial sample 1); while Example 1 not only further improved propylene yield but also reduced coke yield (by 0.2%). Example 3 similarly further improved propylene yield and significantly reduced coke yield (by 0.84%). Existing industrial catalytic cracking catalysts have a total liquid yield (corresponding to "LPG + gasoline + diesel" in Table 3) of 83-86%, a coke yield of 6-10%, and a propylene yield of approximately 5%. It can be seen that the catalytic performance of Example 1 is also significantly improved compared to existing industrial catalytic cracking catalysts.
[0065] Table 1 demonstrates that, compared to existing FCC catalysts, the Y molecular sieve synthesized from seed crystals loaded with organic matter provided by this invention has superior effects in improving propylene yield and reducing coke production. This proves that the preparation method of this invention can regulate the structure of the molecular sieve, and the resulting Y molecular sieve, synthesized from seed crystals loaded with organic matter, has excellent catalytic performance.
[0066] This invention improves the skeletal silicon-aluminum ratio and reduces the crystal size of the molecular sieve by treating the starting Y molecular sieve by changing the type and amount of organic ions. This, in turn, enhances the catalytic performance of the molecular sieve. Moreover, the synthesis process is simple and inexpensive, which helps reduce technical costs and facilitates industrial implementation.
[0067] The above content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined by the present invention, and all such modifications or additions should fall within the protection scope of the present invention.
Claims
1. A method for preparing a Y-type molecular sieve, comprising the following steps: (1) The starting Y molecular sieve is impregnated with a solution of quaternary ammonium compound to introduce quaternary ammonium ions into the molecular sieve pores, thereby obtaining Y molecular sieve seed crystals with a protected framework. (2) The silicon source, aluminum source, alkali, and Y molecular sieve seed crystals with a protected framework are uniformly mixed with water to obtain a mixed gel; (3) The mixed gel is transferred to a high-temperature crystallization kettle for crystallization to obtain the Y molecular sieve product; In step (1), the silica-alumina ratio of the initial Y molecular sieve framework is not less than 2.0; the quaternary ammonium compound mentioned in step (1) is a quaternary ammonium salt or a quaternary ammonium base; the treatment conditions in step (1) are, by mass ratio, initial Y molecular sieve: quaternary ammonium compound: solvent = (0.1~1): (0.01~1): (0.01~100); In step (2), the mass ratio of silicon source: aluminum source: alkali: Y molecular sieve seed crystals with protected framework: H2O is (0.1-3): (0.1-1): (0.01-2): (0.01-1): (0.5-50). In step (3), the crystallization temperature is 50-120℃, the processing time is 0.1-240h, and the pressure is 0.1-10Mpa; the crystallization process is selected from one or more of hydrothermal crystallization, solid-like phase crystallization, steam-assisted crystallization, and atmospheric pressure rotational crystallization.
2. The method according to claim 1, characterized in that... In step (1), the framework silica-alumina ratio of the initial Y molecular sieve is not less than 3.0, and the framework silica-alumina ratio is determined by X-ray fluorescence spectroscopy analysis. There are no special requirements for the crystallinity of the initial Y molecular sieve in step (1).
3. The method according to claim 1, characterized in that... Step (1) The initial crystallinity of the Y molecular sieve is 60-100.
4. The method according to claim 1, characterized in that... Step (1) The initial crystallinity of the Y molecular sieve is 70-100.
5. The method according to claim 1, characterized in that... Step (1) The initial crystallinity of the Y molecular sieve is 80-95.
6. The method according to claim 1, characterized in that... The quaternary ammonium compound mentioned in step (1) is one or more of tetrapropylammonium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium bromide, tetraethylammonium bromide, and tetramethylammonium bromide; the solvent used in the solution is water or a low-carbon alcohol.
7. The method according to claim 6, characterized in that... The solvent used in the solution in step (1) is one of ethanol, propanol, or ethylene glycol.
8. The method according to claim 1, characterized in that... The impregnation treatment in step (1) is selected from one or more of the following methods: over-impregnation, equal-volume impregnation, multiple impregnation, impregnation sedimentation, fluidized bed spray impregnation, impregnation vapor phase impregnation, vacuum impregnation, and pressurized impregnation. In the impregnation process described in step (1), the mass ratio of the initial Y molecular sieve to the quaternary ammonium compound is not less than 0.
1.
9. The method according to claim 8, characterized in that... In step (1) impregnation, the mass ratio of the initial Y molecular sieve to the quaternary ammonium compound is not less than 1.
10. The method according to claim 9, characterized in that... In step (1) impregnation, the mass ratio of the initial Y molecular sieve to the quaternary ammonium compound is not less than 2.
11. The method according to claim 1, characterized in that... In step (2), the mass of the Y molecular sieve seed crystals whose framework is protected should not exceed 50% of the total material mass. The silicon source mentioned in step (2) is one or more of tetraethyl orthosilicate, fumed silica, water glass, silica sol, and coarse-pore silica gel; The aluminum source mentioned in step (2) is one or more of aluminum sulfate, aluminum nitrate, aluminum powder, sodium aluminate, aluminum hydroxide powder, and boehmite; The alkali added to the gel in step (2) is an inorganic alkali or an organic alkali; the inorganic alkali is one or more of LiOH, NaOH, and KOH; the organic alkali is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, choline hydroxide, tetrapropylammonium bromide, hexadecyltrimethylammonium bromide, triethylamine, and ethylenediamine.
12. The method according to claim 11, characterized in that... In step (2), the mass of the Y molecular sieve seed crystals with the skeleton protected should not exceed 30% of the total material mass.
13. The method according to claim 12, characterized in that... In step (2), the mass of the Y molecular sieve seed crystals whose framework is protected should not exceed 20% of the total material mass.
14. The method according to claim 1, characterized in that... The crystallization process in step (3) is selected from one or more of hydrothermal crystallization, solid-like phase crystallization, steam-assisted crystallization, and atmospheric pressure rotational crystallization.
15. A catalyst prepared using the method described in any one of claims 1-14.
16. A method for fluidized catalytic cracking using a catalyst prepared by any one of claims 1-14 or a catalyst as described in claim 15.
Citation Information
Patent Citations
Preparation method of high-silicon Y molecular sieve by seed crystal method
CN111825104A
Process for preparing a high silica faujasite aluminosilicate, ECR-4
US4714601A
Process for preparing a high silica zeolite having the faujasite topology, ECR-32
US4931267A
Preparation method for high-dispersion zeolite molecular sieves
CN103204515A
Method for preparing composite molecular sieve
CN109437230A